2020
DOI: 10.32479/ijefi.9069
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology and Systemic Risk

Abstract: This paper examine the effect of financial institutions management information system migration to blockchain technology on systemic risk. Our study examines a sample of 40 financial institutions around the world. The aim is to identify to what extent the migration of financial company management information system to blockchain system contribute to minimize systemic risk measures through regressions on panel data. We have reached the empirical evidence which indicates that the change we mentioned earlier affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A huge stream of research has investigated the ME in developed markets (Antounian et al, 2021;Garfatta and Zorgati, 2021;Guthrie, 2021;Kachouri et al, 2020;Ji et al, 2019;Nazaridavaji and Khoramabad, 2021;Wang et al, 2021). Although very few studies have addressed this construct in emerging markets (Miri et al, 2021;Salehi et al, 2020), specially the Tunisan one (Marouan, 2015;Mohammadi and Khodabandehlu, 2019;Mselmi and Regaieg, 2017). Hence, our study will shed additional light in this area knowing the notable differences in institutional setting (Surroca et al, 2020) and corporate governance structure (Ji et al, 2019;Sallemi et al, 2021) between developed and emerging markets (Ighodalo et al, 2021;Ghaleb et al, 2021).…”
Section: Rq How Do Firm Characteristics and Audit Quality Affect Me?mentioning
confidence: 84%
See 1 more Smart Citation
“…A huge stream of research has investigated the ME in developed markets (Antounian et al, 2021;Garfatta and Zorgati, 2021;Guthrie, 2021;Kachouri et al, 2020;Ji et al, 2019;Nazaridavaji and Khoramabad, 2021;Wang et al, 2021). Although very few studies have addressed this construct in emerging markets (Miri et al, 2021;Salehi et al, 2020), specially the Tunisan one (Marouan, 2015;Mohammadi and Khodabandehlu, 2019;Mselmi and Regaieg, 2017). Hence, our study will shed additional light in this area knowing the notable differences in institutional setting (Surroca et al, 2020) and corporate governance structure (Ji et al, 2019;Sallemi et al, 2021) between developed and emerging markets (Ighodalo et al, 2021;Ghaleb et al, 2021).…”
Section: Rq How Do Firm Characteristics and Audit Quality Affect Me?mentioning
confidence: 84%
“…, 2021; Salehi et al. , 2020), specially the Tunisan one (Marouan, 2015; Mohammadi and Khodabandehlu, 2019; Mselmi and Regaieg, 2017). Hence, our study will shed additional light in this area knowing the notable differences in institutional setting (Surroca et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent events have also proven blockchain technology's utility as stated by Garrick Hileman, visiting fellow at the London School of Economics, in a recent interview 12 : "When critical infrastructure is out or there are concerns about how quickly something can get through traditional banking system, as long as you have internet and a computing device you can transact." Consequently, there is the possibility of minimizing the systemic risks as Blockchain is a decentralized financial system that is independent of local political instability (Mselmi, 2020).…”
Section: Reducing Systemic Infrastructure Finance Risksmentioning
confidence: 99%
“…Second, The primary purpose of this article is to offer a full picture of the need for fast, fair, and safe HL and how this can be achieved. [124] found that BCT and IoT expedite innovation and technical progress in financial security. Indeed, these technologies have established themself in the finance world and have succeeded not only to minimize operational risk but also systemic risk.…”
Section: B Practical Contributionmentioning
confidence: 99%